#TITLE_ALTERNATIVE# - NUR HIDAYAT (NIM : 13206059); pembimbing :Dr. Effrina Yanti Hamid, ST,MT ; Trio Adiono , ST, MUHAMAD
Digital Audio Broadcasting ( DAB ) standard is one example of many wireless communication technology being deployed nowadays. In wireless communication , system has to recover the degradation effect from the propagation channel .The effect of the propagation channel could be eliminated by using channel estimation and equalization . In this final project, the effect of the channel estimation and equalization with Least Square algorithm is analyzed in DAB signal transmission using MATLAB R2010a software. Channel model ITU-R M1225 is used for this simulation , with varying receiver speed to add the Doppler effect of the channel . As a result, the DAB system performance without channel estimation and equalization with LS algorithm still show exceptable result . For frequency selective fading channel , system performance is still exceptable for a few transmission mode although it is still worse than DAB system in flat fading channel performance. The DAB system using channel estimation and equalization shows good performance after a particular Signal to Noise Ratio ( SNR ) . The channel estimation and equalization algorithm could improve the DAB system performance in selective fading channel, especially for large SNR.